Dissociation of functional and anatomical brain abnormalities in unaffected siblings of schizophrenia patients. Issue 5 (May 2015) - Guo, Wenbin; Song, Yan; Liu, Feng; Zhang, Zhikun; Zhang, Jian; Yu, Miaoyu; Liu, Jianrong; Xiao, Changqing; Liu, Guiying; Zhao, Jingping
Highlights A dissociation phenomenon suggested that brain functional and anatomical abnormalities might be present independently in unaffected siblings of schizophrenia patients. The recruitment of unaffected siblings offers insight into the pathophysiology of schizophrenia independently of the clinical and treatment issues that complicate studies of the patients themselves. Several possible factors were given to the increase of gray matter volume in the left putamen in the sibling group.